Complement Factor H polymorphism Y402H associates with inflammation, visual acuity, and cardiovascular mortality in the elderly population at large - Mooijaart, Simon P.; Koeijvoets, Kristel M.C.; Sijbrands, Eric J.G.; Daha, Mohamed R.; Westendorp, Rudi G.J. (Experimental gerontology, 2007)
The haplotype tagging Y402H polymorphism in the Complement Factor H gene ( CFH) has consistently been associated with age-related macular degeneration, whereas conflicting results have been reported on its relationship with cardiovascular disease. CFH plays a role in inflammation, which is causal to both diseases and both are highly prevalent in old age. Therefore, we investigated whether or not Y402H associated with inflammation, visual acuity, and cardiovascular disease in old age. Within the Leiden 85-plus Study, a prospective population-based study of participants aged 85 years and older, we found that carriers of the CFH 402HH variant had a higher production of IL-6 in whole blood samples compared to those carrying the 402YY variant ( P = 0.029). Carriers of the 402HH genotype also had a steeper increase in circulating C-reactive protein levels during follow-up ( P = 0.009), lower visual acuity ( P = 0.020), and an increased risk of cardiovascular mortality ( P = 0.004). Subjects in the lowest tertile of visual acuity had a twofold increased risk of cardiovascular mortality compared to those in the highest tertile ( P = 0.001). We conclude that the CFH Y402H polymorphism associates with inflammation, visual impairment, and cardiovascular mortality in the elderly population at large. Visual impairment identifies elderly with an increased risk of cardiovascular disease.